SOME ASPECTS OF CLIMATE MAP CREATION (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article discusses the key aspects of creating climate maps. It highlights the processes of collecting, processing, and analyzing climate data, as well as the main cartographic visualization methods used in climate mapping. The article also addresses the main challenges encountered in creating climate maps and suggests possible solutions. In addition, it provides detailed information about the role of modern GIS technologies and interpolation methods in climate cartography, particularly in enhancing data accuracy and improving the quality of visual information. Furthermore, the article discusses the importance of climate maps in the development of various sectors of the national economy.